Molecular mechanisms in myogenesis and in rhabdomyosarcoma - Sun, Danqiong (Kansas State University, 2010)
Muscle satellite cells are the primary stem cells of postnatal skeletal muscle. Quiescent satellite cells become activated and proliferate during muscle regeneration after injury. They have the ability to adopt two divergent fates: differentiation or self-renewal. The Notch pathway is a critical regulator of satellite cell activation and differentiation. Notch signaling is activated upon the interaction of a Notch ligand present in a signal-sending cell with a Notch receptor present in a signal-receiving cell. Delta-like 1 (Dll1) is a mammalian ligand for Notch receptors. In this study, we found that Notch activity is essential for maintaining the expression of Pax7, a transcription factor associated with self-renewing satellite cells. We also demonstrated that Dll1 represents a substrate for several ADAM metalloproteases. Dll1 shedding takes place in a pool of Pax7-positive self-renewing cells, but Dll1 remains intact in differentiated myotubes. Inhibition of Dll1 shedding with a dominant-negative form of ADAM12 leads to elevated Notch signaling, inhibition of differentiation and expansion of the pool of self-renewing cells. We propose that ADAM-mediated shedding of Dll1 helps achieve an asymmetry in Notch signaling in initially equivalent myogenic cells and helps sustain the balance between differentiation and self-renewal. Pax7 plays a key role in protecting satellite cells from apoptosis. The mechanism of Pax7 protecting muscle satellite cells from apoptosis is not well understood. In the second part of this study, we show that Pax7 up-regulates manganese superoxide dismutase (MnSOD) at the transcriptional level, suggesting the involvement of MnSOD in Pax7-mediated cell survival. A specific chromosomal translocation involving the Pax7 gene and generation of a fusion protein Pax7-FKHR is found a childhood cancer, rhabdomyosarcoma. Furthermore, the level of the wild-type Pax7 is down-regulated in rhabdomyosarcomas. In the third part of this dissertation, we investigated the dominant-negative effect of Pax7-FKHR fusion protein on the wild-type Pax7, and found that the Pax7 protein level is down-regulated by Pax7-FKHR expression while the Pax7 mRNA level is not affected. We propose a specific microRNA-mediated inhibition of Pax7 mRNA translation by the oncogenic Pax7-FKHR fusion protein.
Keywords: Stem cells; Muscle; Cell signaling; Proteolysis; Gene expression; Cancer; Biology, Cell (0379); Biology, Molecular (0307); Chemistry, Biochemistry (0487)